EFFECTS OF ROSEMARY (Rosmorinus officinalis) LEAVES AND ITS VOLATILE OILS ON WHEAT DOUGH PROPERTIES AND BREAD SHELF LIFE. - jamil, Dara Muhamad; saed, Mohammad wajeeh Mohammad; Jaffar, Sahar Ahamad (Sulaimani Journal for Pure and Applied Sciences, 2015)
The effects of ground rosemary leaves (2.5, 5, and 10%) and rosemary volatile oil (0.1, 0.2 and 0.4%), on wheat dough rheology, fermentation and its bread quality were studied. Amylograph results showed a decrease in pasting temperature from 63°C to 61.5°C in all VO doses. Also amylograph results showed ground leaves had an inhibitory effect on dough α-amylase especially at 2.5%. Farinograph results showed only 0.1% VO had a significant effect on farino parameters while other treatments generally had a softening effect. Dough fermentation values were decreased at all doses of ground leaves and VOs except for 0.2% VO which had an activation effect. Also the dough and loaf volume/weight were also decreased at all doses. The loaf shelf life was dose dependent and significantly increased against mould growth up to thirty days storage.
Keywords: rosemary leaves; rosemary volatile oil; wheat dough rheology; dough fermentation; loaf shelf life